Progesterone effects on the oligodendrocyte linage: all roads lead to the progesterone receptor - Jure, Ignacio (2019)
A new role has emerged for progesterone after discovering its potent actions away from reproduction in both the central and the peripheral nervous system. The aim of the present report is to discuss progesterone’s mechanisms of action involved in myelination, remyelination and neuroinflammation. The pivotal role of the classic progesterone receptor is described and evidence is compiled about progesterone’s direct effects on oligodendrocyte linage and its indirect effects on oligodendrocyte precursor cell differentiation by decreasing the neuroinflammatory environment.